Evidence-based OTC “Prescribing”—A New Postgraduate Course at the Auckland School of Pharmacy - Sheridan, J.; Shaw, J.; Hancox, D. (Pharmacy Education, 2003)
The School of Pharmacy at the University of Auckland has recently developed a taught postgraduate course, evidence-based over-the-counter (OTC) prescribing, aimed specifically at community pharmacists and designed to develop the skills required to practise evidence-based medicine (EBM) utilising OTC “pre- scribing” as the vehicle for learning. The course forms an optional part of the postgraduate pharmacy programme available at the University of Auckland including PGCert/PGDip/Masters of Pharmacy Practice programmes and is designed to build on a compulsory course in clinical skills. This report describes the course objectives, course structure and assessments. Views of students are also presented.